Numerical Study on Pipeline Pressure Surge of the Large Aircraft Fuel System - Yi Tu; Xuanren Chen; Liang Yin; Qiuyun Zheng; Yu Zeng (Shock and Vibration)
The sudden closure of the refueling valve during the refueling process will cause the water hammer phenomenon in the pipeline of the large aircraft fuel system and produce pressure waves propagating along the pipeline. In serious cases, it will cause severe damage to the pipeline. The pressure surge in the pipeline can be affected by many design factors. In this study, the numerical modeling method of the large aircraft fuel system is studied using the Flowmaster program, and the accuracy of steady and transient state analysis of the simulation method is verified by experimental data. Based on this numerical method, a complete system-level simulation model of the large aircraft fuel system was established. Using this model, the effects of valve closure speed, diameter of the refueling main pipe, and refueling volume flow rate on pipeline pressure surge during the refueling process are investigated. The results indicate that all three factors have a significant impact on the pipeline pressure surge of the fuel system. The effect of the valve closing speed and the pipe diameter on the pressure surge of the pipeline is nonlinear and gradually weakened with the decrease of valve speed and the increase of pipe diameter, while the effect of refueling volume flow rate on the pipeline pressure surge is approximately linear.